2021
DOI: 10.1590/0034-7167-2020-0511
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of educational material on promoting breastfeeding in schools

Abstract: Objective: to build and validate an educational technology on the promotion of breastfeeding for schoolchildren. Methods: a methodological study was developed through a bibliographic survey, situational diagnosis, creation of illustrations, layout, design and texts, validation of the material with the help of expert judges and target audience. Results: the content judges enabled the validation of the material with an overall Content Validity Index of 90%, the judges of the design Suitability Assessment of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…O aplicativo obteve IVC médio global de 0,96, apresentando validade, em consonância com outros estudos de validação de tecnologias educacionais, como um material educativo, em forma de história em quadrinhos, sobre promoção do aleitamento materno em escolares (28) . Os IVC individuais obtiveram níveis satisfatórios, assim, o aplicativo é organizado, de fácil leitura e manuseio, e possui conteúdo atualizado.…”
Section: Resultsunclassified
“…O aplicativo obteve IVC médio global de 0,96, apresentando validade, em consonância com outros estudos de validação de tecnologias educacionais, como um material educativo, em forma de história em quadrinhos, sobre promoção do aleitamento materno em escolares (28) . Os IVC individuais obtiveram níveis satisfatórios, assim, o aplicativo é organizado, de fácil leitura e manuseio, e possui conteúdo atualizado.…”
Section: Resultsunclassified
“…In the present study, educational rating by target users and experts was not performed by the same tool, since the research team found it difficult for users to use PEMAT and SAM tools. Therefore, a checklist adapted from previous studies was provided for the users, which consisted of simple and understandable questions [31,32,44]. In this study, only one patient (3.33%) was not interested in the material's content.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research were similar to other studies on educational technologies on breastfeeding in Brazil, such as an educational video validated regarding its functionality, usability, efficiency, audiovisual technique, environment, procedure, objectives, organization, video style, appearance and motivation, which obtained an overall rating of 100% by the target audience, and can be used to encourage this practice among families ( 27 ) . Another investigation that sought to evaluate educational material in the format of a comic book about breastfeeding with children between seven and nine years of age obtained an agreement rate of 95.6% in the evaluation by the target audience, thus revealing itself to be a valid and reliable instrument to be used with schoolchildren in order to promote the culture of breastfeeding ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%